Kajian Pengembangan Aplikasi Sistem Informasi Jabatan Fungsional - Hutapea, Sabungan Halomoan; Sinaga, Rosita (Warta Penelitian Perhubungan, 2010)
The lnfonnation and data center (Pusdatin) ofT71£ Ministry of Transportation has developed personnelinformation StJSfem to meet the needs of infonnation of Personnel Bureau of Ministn; of Transportation.T1ie llVlilability of information prepared btJ Pusdatin, has not yet meets tliese needs particularlyabout researcl7er's functional position.The proress of achieving functional position follows tl1£ applied rules and procedures, and involvesmany related agena; whiclz is timely consumed nnd d~fjirnlt to monitor numunlly.We shouldn't Jun~ faced tl10se problems in this web based infomuition technologtj era.The development of data base to support 1reb based infonnation is expected to provide reliable, quickinformation, and also simplicity in monitoring tlie process.This studt; is a researcl1 on data base conrept nnd derielops an application, which will be implementedto pT01ii£le n~b based infon1llltion relnted to nsenrcher's fimctionnl position. 77ie der~loped applicationuses Database MySQL nnd programming in: PHP mid HTML.The result of this studt; can be acassed from internet: http;//andwah2freehostia.com